Ayotzinapa. Urgent Reflections to End the Perpetuity of Violence. Review by: ALONSO REYNOSO Carlos. (2025). AYOTZINAPA. Un movimiento digno, persistente e indómito. Cátedra Interinstitucional. Universidad de Guadalajara-CIESAS-Jorge Alonso. 776pp. - de PARRES GÓMEZ, Francisco (Utopía y Praxis Latinoamericana, 2025)
The book Ayotzinapa. Un movimiento digno, persistente e indómito [Ayotzinapa. A Dignified, Persistent, and Indomitable Movement], by Carlos Alonso Reynoso, offers a rigorous and committed analysis of one of the most emblematic cases of enforced disappearance in Mexico. Based on a documented and critical chronicle, the work reconstructs the events since 2016 surrounding the 43 disappeared students from the Ayotzinapa Rural Normal School, contextualizing the tragedy within a framework of structural violence, impunity, and collusion between the state and organized crime. The author examines the political, social, and cultural dimensions of the case, the persistent struggle of the families for truth and justice, as well as the national and international implications that reveal a deep human rights crisis in Mexico. This text becomes a key tool for understanding enforced disappearances in Latin America and the social resistance demanding memory, reparation, and structural transformation.